(untitled) - Slater, Jeffrey (Boston, 2011)
This text presents a comprehensive introduction to the concepts & applications of mathematics to personal & commercial business problems. It uses basic arithmetic & problem solving techniques & illustrates their use in retailing, interest & loans, banking, payroll, taxes, investments, insurance & a variety of other business situations.
Keywords: Business mathematics,Toán kinh tế